2022
DOI: 10.3389/fimmu.2022.838448
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Induces Cytokine Responses in Human Basophils

Abstract: Basophils play a key role in the orientation of immune responses. Though the interaction of SARS-CoV-2 with various immune cells has been relatively well studied, the response of basophils to this pandemic virus is not characterized yet. In this study, we report that SARS-CoV-2 induces cytokine responses and in particular IL-13, in both resting and IL-3 primed basophils. The response was prominent under IL-3 primed condition. However, either SARS-CoV-2 or SARS-CoV-2-infected epithelial cells did not alter the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Previous studies have suggested that the primary role of eosinophils (EOS) and basophils (BAS) is associated with anti-parasitic and allergic reactions. Later, antiviral effects of EOS and BAS were confirmed, which were mainly reported in severe acute respiratory syndrome coronavirus 2 (SARS-COV-2), human immunodeficiency virus (HIV), influenza A viruses, and respiratory syncytial virus (RSV) [ 16 22 ]. Our retrospective study found significant differences in EOS% and BAS% of patients who were weakened compared with those who survived.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that the primary role of eosinophils (EOS) and basophils (BAS) is associated with anti-parasitic and allergic reactions. Later, antiviral effects of EOS and BAS were confirmed, which were mainly reported in severe acute respiratory syndrome coronavirus 2 (SARS-COV-2), human immunodeficiency virus (HIV), influenza A viruses, and respiratory syncytial virus (RSV) [ 16 22 ]. Our retrospective study found significant differences in EOS% and BAS% of patients who were weakened compared with those who survived.…”
Section: Introductionmentioning
confidence: 99%
“…A type 3 hypersensivity has also been evoked in these patients as repeated doses of SARS-CoV2 mRNA vaccine could lead to an immune complex-linked complement activation with a continuous C3a-and C5a-driven basophil activation. 9 In conclusion, our observation of persistent urticaria fulfilling criteria for CSU in close temporal relation with repeated vaccination against SARS-CoV2 suggests a link between the two, which could be of allergic nature. The potential sensitization to vaccine excipients highlighted by the CD63 activation on basophils in some patients not only to the whole vaccine, but frequently also to polysorbate-80, urges the need for more studies investigating the possibility of sensitization to vaccine excipients by repeated immunization in predisposed individuals.…”
Section: Ta B L Ementioning
confidence: 62%
“…A type 3 hypersensivity has also been evoked in these patients as repeated doses of SARS‐CoV2 mRNA vaccine could lead to an immune complex‐linked complement activation with a continuous C3a‐ and C5a‐driven basophil activation. 9 …”
Section: Tablementioning
confidence: 99%
“…PD-L1 expression by basophils is known in humans and may be induced by IFNγ 37 . PD-L1 upregulation on human basophils has recently been described during SARS-CoV2 infections 38 although it is not directly induced by the virus 39 . Interestingly, basopenia occurs in acute SARS-CoV2 infection suggesting putative recruitment of basophils to SLO 40 .…”
Section: Discussionmentioning
confidence: 98%